The Desert Fayum Reinvestigated : the Early to Mid-Holocene Landscape Archaeology of the Fayum North Shore, Egypt. - Holdaway, Simon J. (Monumenta Archaeologica Ser., 2017)
"The Neolithic in Egypt is thought to have arrived via diffusion from an origin in southwest Asia. Here we suggest an alternative approach to understanding the development of food production in Egypt based on the results of new fieldwork in the Fayum, with the results of a detailed study of the Fayum archaeological landscape using an expanded version of low-level food production to organize observations concerning paleoenvironment, socioeconomy, settlement, and mobility. While domestic plants and animals were indeed introduced to the Fayum from elsewhere, when a number of aspects of the archaeological record are compared, a settlement system is suggested that has no obvious analogues with the Neolithic in southwest Asia. The results obtained from the Fayum are used to assess other contemporary sites in Egypt."--Publisher summary.